The role of STAT3 and AhR in the differentiation of CD4+ T cells into Th17 and Treg cells. Issue 17 (April 2017) - Liu, Xingxing; Hu, Hui; Fan, Heng; Zuo, Dongmei; Shou, Zhexing; Liao, Yi; Nan, Zhen; Tang, Qing
Abstract: Background: This study aimed to investigate the role of aryl hydrocarbon receptor (AhR) and STAT3 gene during the differentiation of cluster of differentiation (CD)4 + T cells into T helper (Th)17 and T regulatory (Treg) cells. Methods: First, CD4 + T cells were isolated from the spleen of BALB/c mice. Then, stable CD4 + T cells expressing STAT3 shRNA were constructed. CD4 + T cells were assigned to one of the following treatments: Th17 group: antibodies against CD3 and CD28, 2.5 ng/mL transforming growth factor β (TGF-β)1, 30 ng/mL interleukin (IL)-6, and 30 ng/mL IL-23; 6-formylindolo[3, 2-b]carbazole (FICZ) group: antibodies against CD3 and CD28, 2.5 ng/mL TGF-β1, 30 ng/mL IL-6, 30 ng/mL IL-23, and 100 nM FICZ; FICZ + STAT3 RNAi group (shSTAT3 group): antibodies against CD3 and CD28, 2.5 ng/mL TGF-β1, 30 ng/mL IL-6, 30 ng/mL IL-23, 100 nM FICZ, and STAT3 RNAi; naphthoflavone group: antibodies against CD3 and CD28, 2.5 ng/mL TGF-β1, 30 ng/mL IL-6, 30 ng/mL IL-23, and 3 μM naphthoflavone; 5) no antibodies were added in the control group. Later, the proportions of Th17 and Treg cells in each group were measured by flow cytometry; phospho-STAT3 and -STAT5 levels were measured by western blotting; and AhR, STAT3, STAT5, receptor-related orphan nuclear receptor γt (RORγt), FOXP3, T-cell receptor (TCR), CD25, IL-6R, IL-10, and IL-17 mRNA levels were also measured by real-time PCR. Result: Th17 cells showed a rise and Treg cells showed a decrease in the FICZ group, but revised in the shSTAT3 group and the naphthoflavone group. Significant differences were observed in CD25, IL-6R, IL-10, and IL-17 mRNA levels among different groups. Conclusion: STAT3 may cooperate with AhR to regulate the differentiation of both Th17 and Treg cells.